2021
DOI: 10.1186/s12860-021-00360-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 promotes Schwann cell proliferation and migration via αvβ3 integrin

Abstract: Background Schwann cells (SCs) play a crucial role in the repair of peripheral nerves. This is due to their ability to proliferate, migrate, and provide trophic support to axon regrowth. During peripheral nerve injury, SCs de-differentiate and reprogram to gain the ability to repair nerves. Cysteine-rich 61 (Cyr61/CCN1) is a member of the CCN family of matrix cell proteins and have been reported to be abundant in the secretome of repair mediating SCs. In this study we investigate the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, the targets of AUF1 are likely to be cell-type specific. Querying published papers revealed a number of genes that could be the exact targets for AUF1 that lead to cell proliferation, including AMH, SPARC, FOXG1, CYR61, PLSCR1 and SP100 (37)(38)(39)(40)(41)(42). These genes were explored by RNA-Seq in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the targets of AUF1 are likely to be cell-type specific. Querying published papers revealed a number of genes that could be the exact targets for AUF1 that lead to cell proliferation, including AMH, SPARC, FOXG1, CYR61, PLSCR1 and SP100 (37)(38)(39)(40)(41)(42). These genes were explored by RNA-Seq in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has indicated numerous methods that could promote the proliferation and migration of SCs [35][36][37]. However, these methods frequently involve in complex, difficult to be popularized, and what is more, these factors cannot enhance SC proliferation in the early stage by one hand and further promote SC migration in the late stage by the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Besides NTFs, a number of other biological agents have emerged that show regenerative properties in neurodegenerative diseases, such as vascular endothelial growth factor (VEGF) [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ], insulin-like growth factors (IGFs) [ 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 ], the cellular communication network (CCN) family [ 204 , 205 , 206 , 207 , 208 ], and erythropoietin (EPO) [ 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ], with varying, but also promising results.…”
Section: Challenges and Future Perspective Of The Use Of Ntfs In Neur...mentioning
confidence: 99%